MEDITATIONS ABOUT THE MYSTIC OF MATHEMATICAL LANGUAGE - Pagliacci, Mario G.R. (CEP USM, 2020)
Mathematics is the science of measurement of greatness and form. It is fundamental for trying to understand, describe and explain phenomena, especially when they are chaotic and complex. Mathematical language is not true or false for itself. It is neutral in respect of truth or falsity of the described phenomena. However, it can give a distorted representation of reality when it is utilized in not correct way, by doing conceptual forcing or large approximations. Quantitative language can suggest in inexpert minds that anything is expressed in quantitative statement is more credible than qualitative one. The mystic conception that mathematical language is synonym of truth is confuted.
PAGLIACCI, Mario G.R.. Meditations about the mystic of mathematical language. In: Şcoala internaţională de metodologie în ştiinţele socio-umane. Dezvoltarea personală și educația pentru societate: temeiuri epistemologice actuale: conferinţa știinţifică internaţională, ediţia a 4-a, 19-20 noiembrie, 2020. Chișinău: CEP USM, 2020, p. 92.
Keywords: mathematics; phenomena; mathematical language; truth; falsity; quantitative language